Argumentative Scheme for Abduction - A. S. Bobrova (Дискурс, 2023)
Introduction. The paper scrutinizes abduction through the lens of the argumentation theory. Abduction is treated as an argument with a special argumentative scheme. Argumentation schemes are seen as stereotypical patterns of common types of arguments used in everyday discourse. The main issue of this publication is to specify the scheme of abductive argument and supply it with so-called critical questions. Such questions should identify, reconstruct and evaluate abduction in dialogs.Methodology and sources. At first, I analyze D. Walton and S. Yu & F. Zenker’s patterns of abductive argument, scrutiny their advantages and disadvantages. Then, based on the results of relatively new logical and philosophical investigations, I systemize the peculiarities of abduction. The role of D. Gabbay and J. Wood’s model is especially emphasized.Results and discussion. Both approaches (D. Walton and S. Yu & F. Zenker) are not free of problems. However, several recent logico-epistemological specifications of abduction can reduce them. I mean the position that abduction preserves ignorance and presumes J. Wood’s conclusionality relation. This reasoning is weak and cannot be distinguished from other arguments. These proposals and almost unknown (with interrogative conclusion) Ch. S. Peirce’s scheme of abduction produce a core of argumentative scheme.Conclusion. I provide a version of argumentative scheme of abduction with the set of critical questions. Its formal structure is defined as a move from the consequent to antecedent with the investigand mood conclusion while the material side is seen as reasoning from surprise to investigation. Modified D. Gabbay and J. Wood’s model clarifies the controversial aspects of this argumentative scheme. It also specifies critical questions functions since they lose their traditional role of evaluation.